Modified Ross score and echocardiographic score in children with heart failure: a subgroup analysis - Setiyawan, I Made Karma; Kartika Yantie, Ni Putu Veny; Widnyana, Anak Agung Ngurah Ketut Putra; Sidiartha, I Gusti Lanang; Karyana, Putu Gede; Arimbawa, I Made (Paediatrica Indonesiana, 2024)
Background Over the past two decades, heart failure in children has increased in terms of symptom recognition and prevalence. The initial clinical manifestations of heart failure in children are non-specific. Therefore, diagnosis requires the support of echocardiography. The symptomatic severity of heart failure in children can be classified through a simple scoring system such as Ross score. The duration of heart disease, duration of therapy, and cardiac remodeling status may have clinical and anatomical effects on the disease. Objective To analyze for a possible correlation between modified Ross score and echocardiographic score by subgroup analysis consisting of duration of heart disease, duration of therapy, and cardiac remodeling. Methods This cross-sectional study included children aged 1 month - 18 years with heart failure who sought treatment at Prof.Dr. I.G.N.G Ngoerah Hospital, Denpasar from June 2019 to February 2020. Cardiac remodeling was defined as >20% increase in left ventricle internal end diastolic dimension (LVIDd) compared to normal values, ??based on body surface area. Spearman’s correlation test was used for statistical analysis. Results A total of 30 subjects were analyzed in this study. The median modified Ross score and echocardiography score were 3 points (range 2-11) and 4 (range 2-6), respectively. The median durations of heart disease and preventive heart failure therapy were 2 years (range 7 days-15 years) and 1 year (range 7 days-15 years), respectively. The mean LVIDd was 4.3 (SD 1.4) cm. Twenty-one out of 30 subjects experienced a ? 20% increase of LVIDd from baseline. The modified Ross score and echocardiographic score had no significant correlation (r=0.18; P=0.33). However, the modified Ross score had significant correlations with duration of heart disease (r=-0.632; P<0.001) as well as duration of therapy (r=-0.584; P=0.001). In addition, no correlation was found between echocardiographic score with heart disease and therapy duration (P>0.05). Echocardiography score and remodelling process was significantly correlated (r=0.64; P<0.001). Conclusion There is no correlation between modified Ross score and echocardiographic score. Duration of heart disease and duration of therapy are significantly negatively correlated with modified Ross scores. The remodelling process is positively correlated with echocardiographic score. Further research on acute symptomatic and validated echocardiographic scores are needed.